Disrupted Causal Connectivity Anchored on the Right Anterior Insula in Drug-Naive First-Episode Patients With Depressive Disorder - Xie, Haiyan; Guo, Qinger; Duan, Jinfeng; Jia, Xize; Zhou, Weihua; Sun, Haozhe; Fang, Ping; Yang, Hong (Frontiers in Psychiatry, 2022)
Background:Using coefficient-based general component analysis with the anterior portion of the right insula as a seed point, this study examines abnormalities in the causal connectivity between the SN and whole brain and their correlations to cognitive and mental performance in drug-naive first-episode patients with major depressive disorder (MDD) in the resting state. Methods: Based on the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) diagnostic criteria, 23 drug-naive first-episode MDD patients and 20 matched healthy individuals were recruited and underwent a resting-state magnetic resonance scan. The acquired functional image data were preprocessed using resting-state fMRI data analysis toolkit plus (RESTplus). Using a coefficient-based general component analysis with the rAI as the seed point, the causal connectivity of the SN in the resting state with the whole brain and its correlation with cognitive and mental performance were examined using the data processing & analysis for brain imaging (DPABI) software . Results: 1) The MDD group showed a significantly higher Hamilton Depression Rating Scale total score and significantly higher scores for anxiety, cognitive disturbance, and block factors compared with normal controls. 2) From whole brain to the seed point, the MDD group showed a lower causal connectivity than the control group in the left inferior frontal gyrus; from the seed point to the whole brain , compared with control, the MDD group showed a lower causal connectivity in the right cingulate gyrus, the right precuneus and the paracentral lobule but higher causal connectivity in the left inferior and middle frontal gyrus. 3) In the MDD group, from the seed point to the whole brain, the causal connectivity values for the right cingulate gyrus, the right precuneus, and the paracentral lobule were negatively correlated with the score of Stroop test cards A, B, and C as well as interference times. Conclusion: Our results indicated disrupted causal connectivity among the default mode network, the central executive network and SN in first-episode MDD patients . Especially, our results suggests a unique role for rAI in the ordered or hierarchical information processing, presumed to include bottom-up and top-down reciprocal influences among the three networks in MDD.